FAKTOR-FAKTOR YANG MEMPENGARUHI NERACA PEMBAYARAN INDONESIA - Amanda C. Anisa; Yusbar Yusuf; Anthony Mayes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the factors that affect Indonesia's balance of payments in 1996-2015. The study consists of three independent variables (exchange rates, gross domestic product, and net exports) and one dependent variable (balance of payments). Indonesia's balance of payments (BOP) is the listing on the economic transactions that occur between the population and not the population of Indonesia in a certain period. The data used are annual data from the years 1996-2015. The analytical method used is multiple linear regression using SPSS version 20.0. The research results obtained are exchange rates, gross domestic product, and net exports together (simultaneously) the effect on the balance of payments with a significance level of 5%. Partially exchange rates had a negative effect on the balance of payments, while the variable gross domestic product and net exports partially positive effect on the balance of payments. Variation factors that affect the balance of payments is explained by exchange rates, gross domestic product, and simultaneously affect net exports amounted to 52.3% (R2 = 0.523), while the remaining 47.7% is explained by other variables not included in this study. Between exchange rates, gross domestic product, and net exports, those three independent variables have significant effect on the balance of payments.Keywords : Balance of Payments, Exchange Rate, Gross Domestic Product, Net Exports